Lower leg vascular conductance in triathletes - Namatame, H.; Tayama, H.; Maeda, S.; Otsuki, T. (The Journal of Physical Fitness and Sports Medicine, 2025)
Triathlon is an endurance sport that requires high aerobic capacity. Previous studies demonstrated that lower-leg vascular conductance (VC) was associated with maximal oxygen uptake. However, it is unclear whether muscular VC is greater in triathletes versus untrained individuals. To test our hypothesis that VC in skeletal muscle is greater in triathletes relative to untrained peers and is associated with higher aerobic capacity in triathletes, this study investigated 10 male triathletes (21 ± 1 years of age) and 8 untrained men (22 ± 1 years). Triathletes exhibited greater maximal oxygen uptake than their untrained counterparts (61 ± 6 vs. 39 ± 6 mL/kg/min, p < 0.01), as well as lower heart rate (54 ± 7 vs. 65 ± 9 bpm, p = 0.01) and body fat (11 ± 2 vs. 16 ± 6 %, p = 0.03). There were no detectable intergroup differences in systolic (115 ± 8 vs. 117 ± 9 mmHg, p = 0.74), mean (83 ± 6 vs. 86 ± 8 mmHg, p = 0.30), or diastolic (62 ± 6 vs. 65 ± 7 mmHg, p = 0.49) blood pressure. Lower-leg blood flow (4.2 ± 1.3 vs. 2.5 ± 0.9 mL/dL/min, p = 0.01) and VC (0.05 ± 0.01 vs. 0.03 ± 0.01 mL/dL/min/mmHg, p = 0.02) based on venous occlusion plethysmography were greater in triathletes versus untrained men. Maximal oxygen uptake was correlated with lower-leg blood flow (r = 0.70, p < 0.01) and VC (r = 0.69, p < 0.01). These results demonstrate that lower-leg VC is higher in triathletes than in untrained individuals, and it may be associated with higher aerobic capacity in triathletes relative to their untrained counterparts.